A cryptic Gondwana-forming orogen located in Antarctica - Daczko, N.; Halpin, J.; Fitzsimons, Ian; Whittaker, J. (Nature Publishing Group, 2018)
The most poorly exposed and least understood Gondwana-forming orogen lies largely hidden beneath ice in East Antarctica. Called the Kuunga orogen, its interpolation between scattered outcrops is speculative with differing and often contradictory trends proposed, and no consensus on the location of any sutures. While some discount a suture altogether, paleomagnetic data from Indo-Antarctica and Australo-Antarctica do require 3000-5000 km relative displacement during Ediacaran-Cambrian Gondwana amalgamation, suggesting that the Kuunga orogen sutured provinces of broadly Indian versus Australian affinity. Here we use compiled data from detrital zircons offshore of East Antarctica that fingerprint two coastal subglacial basement provinces between 60 and 130°E, one of Indian affinity with dominant ca. 980-900 Ma ages (Indo-Antarctica) and one of Australian affinity with dominant ca. 1190-1140 and ca. 1560 Ma ages (Australo-Antarctica). We combine this offshore compilation with existing and new onshore U-Pb geochronology and previous geophysical interpretations to delimit the Indo-Australo-Antarctic boundary at a prominent geophysical lineament which intersects the coast east of Mirny at ~94°E.